Respon Pertumbuhan Dan Hasil Tanaman Terung Ungu (Salonum melongena L.) Terhadap Pemberian Mulsa Dan Jarak Tanam Yang Berbeda - Armin Lou Mada; Marten Umbu Nganji (Sandalwood Journal Of Agribusiness And Agrotechnology, 2026)
This study aims to examine the effect of mulching (M) and planting distance (J) on the growth and yield of purple eggplant. The results of the analysis show statistically significant differences in vegetative growth parameters, namely Plant Height and Number of Leaves, in the early phase (28 days after sowing) and middle phase (56 days after sowing) based on the Tukey's Post-hoc Test (BNJ) at 5%. The J1M1 treatment combination yielded the best results at 28 DAP with a plant height of 48.00 cm and a number of leaves of 19.92. At 56 DAP, the M1 Mulch treatment consistently produced the highest values for plant height (48.00 cm) and number of leaves (42.00 leaves). Conversely, in the generative phase, for the parameters Number of Fruits (72 DAP) and Fruit Weight, the 5% BNJ test results showed no significant differences among all treatment combinations. However, descriptively, the Mulsa M1 treatment still showed a tendency to produce the highest number of fruits (average of 8.875 fruits) and fruit weight (average of 156.50971). The main conclusion is that Mulsa M1 proved to be the most effective in optimizing environmental conditions, such as maintaining soil moisture and suppressing weeds, thereby maximally supporting the vegetative and generative growth of purple eggplant plants.